PENYULUHAN PENCEGAHAN PENYAKIT DEGENERATIF PADA MASYARAKAT DUSUN CICURUG, DESA INDRAJAYA, KECAMATAN SUKARATU TASIKMALAYA - Widya Primi Annissya; Anisa Febiansyah; Muhammad Nur Ridwan; Sheila Nurazizah; Erlina Fadilawati; Rovi Dulfikri; Vinka Fitria; Lesa Nandyta; Amalia Fitriani; Aliza Rachmalia Putri; Della Syariah; Rikzan Maulana (Universitas Bakti Tunas Husada, 2025)
The health education program on degenerative disease prevention was conducted in Dusun Cicurug, Indrajaya Village, Tasikmalaya Regency. The program aimed to enhance community awareness of risk factors, preventive measures, and the importance of early detection of hypertension and diabetes mellitus. The implementation consisted of two stages: a presentation of the material and an interactive discussion session, complemented by free health screening services. Program effectiveness was evaluated using pre-tests and post-tests to assess participants’ knowledge improvement. The results indicated a significant increase across all age groups, with the proportion of participants categorized as having “good” knowledge exceeding 88% in the ≥ 65 years group and over 95% in the ≤ 65 years group. Active participation and high enthusiasm from the community were key factors in the program’s success. These findings demonstrate that systematically designed health education involving community engagement can effectively enhance awareness and knowledge in preventing degenerative diseases.